2007
DOI: 10.1007/s10967-007-0507-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-humped fission and fusion barriers of actinide and superheavy elements

Abstract: The energy of a deformed nucleus has been determined within a Generalized Liquid Drop Model taking into account the proximity energy, the microscopic corrections and quasi-molecular shapes. In the potential barrier a third peak exists for actinides when one fragment is close to a magic spherical nucleus while the other one varies from oblate to prolate shapes. The barrier heights and half-lives agree with the experimental data. The different entrance channels leading possibly to superheavy elements are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…In the present work it is found that the introduction of the shell and pairing energy correction, associated with touching ellipsoidal fragments, can reduce the barrier height by several MeV, even lead to a third minimum. [30] Royer et al [30,35,44] pointed out that the third minimum and third peak exist only in the asymmetric decay path and for some specific isotopes, which is in accordance with our study.…”
Section: 4 Pairing Energysupporting
confidence: 93%
“…In the present work it is found that the introduction of the shell and pairing energy correction, associated with touching ellipsoidal fragments, can reduce the barrier height by several MeV, even lead to a third minimum. [30] Royer et al [30,35,44] pointed out that the third minimum and third peak exist only in the asymmetric decay path and for some specific isotopes, which is in accordance with our study.…”
Section: 4 Pairing Energysupporting
confidence: 93%
“…During the last years, the efforts for developing improved models for the calculation of fission barriers were intensified, using the macroscopic-microscopic approach [27,[39][40][41][42][43][44], the density-functional theory [22,45,46] and varieties of Hartree-Fock methods [47][48][49][50]. Still, the results from the different models, in particular in regions, where no experimental data exist, differ appreciably.…”
Section: A Systematics Of Fission Barriersmentioning
confidence: 99%
“…Forced fission of isotopes of heavy mass elements by interaction with thermal neutrons is a complex and multi-factor process. In studying this process, many authors have aimed at developing and describing the fission mechanism [1][2][3][4][5][6][7][8][9][10][11][12][13], sets of the most probable fission fragments [14][15][16][17][18][19] and elementary particles [20][21][22], and total energy balance [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%